A composite coated lithium ion battery positive electrode material and its preparation method and application

By using a composite cladding layer on the positive electrode material of lithium-ion batteries, including conductive polymers and dot-shaped inorganic oxides, the problems of unstable structure and uneven coating of the positive electrode material in the prior art are solved, and better Electrochemical properties and cyclic stability.

CN117996022BActive Publication Date: 2025-02-14CHONGQING TALENT NEW ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311843494.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-28
Publication Date
2025-02-14
Estimated Expiration
2043-12-28

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode materials have structural damage and instability during the charging and discharging cycle, and conventional coating methods are difficult to achieve uniform coating, which affects battery performance and life.

Method used

A composite cladding layer, including conductive polymers and dot-distributed inorganic oxides, is used to form a uniform composite cladding layer on the surface of the core body of the positive electrode active material by template method and liquid phase cladding technology.

Benefits of technology

It improves the transmission performance of lithium ions and electrons, suppresses interface side reactions, enhances the cycle performance and rate performance of the battery, and has a stable coating structure, avoiding functional instability caused by swelling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117996022B_ABST
    Figure CN117996022B_ABST
Patent Text Reader

Abstract

The present invention relates to a composite coated lithium ion battery positive electrode material and a preparation method and application thereof. The composite coated lithium ion battery positive electrode material of the present invention comprises a positive electrode active material core and a composite coating layer coated on the surface of the positive electrode active material core, wherein the composite coating layer comprises a conductive polymer and an inorganic oxide, the inorganic oxide is distributed in a dotted manner on the surface of the positive electrode active material core, and the inorganic oxide distributed in a dotted manner is dispersed in the conductive polymer matrix, extending from the surface of the positive electrode active material core to the surface of the composite coating layer. The composite coated lithium ion battery positive electrode material of the present invention can ensure the electron and ion transmission performance of the lithium ion battery positive electrode material, thereby ensuring the battery capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite-coated cathode material for lithium-ion batteries, belonging to the technical field of lithium-ion batteries. Specifically, the present invention relates to a composite-coated cathode material for lithium-ion batteries, a preparation method thereof, and a lithium-ion battery using the composite-coated cathode material for lithium-ion batteries. Background Art

[0002] As a new type of energy storage device, lithium-ion batteries have advantages such as high voltage, low self-discharge rate, and high energy density, and are thus widely used in fields such as electronic products, transportation, and energy storage. As a cathode material for lithium-ion batteries, the layered ternary material LiNi 1-x M x O2 (0 < x < 0.5, M = Co, Mn, Al) has advantages such as low cost, good safety, and high energy density. Its excellent electrochemical performance makes it one of the most important and widely used cathode materials for lithium batteries. However, in practical applications, the ternary material still has many disadvantages, such as structural damage during charge and discharge cycling, structural instability caused by lithium-nickel mixing, and negative impacts on processing performance and electrical performance caused by residual alkali on the material surface. The interface layer is a key factor in regulating its structural stability and electrochemical performance, directly affecting the cycle performance of the material.

[0003] The surface coating technology constructs a physical barrier on the surface of the cathode material, isolating the direct contact between the active material and the electrolyte, and can construct a stable and firm cathode / electrolyte interface, reducing the dissolution of transition metals and avoiding the decline of electrode performance caused by side reactions between the two.

[0004] In the existing publicly disclosed technical strategies, inorganic materials are mainly used as a single coating layer. However, conventional coating methods are difficult to achieve uniform coating of inorganic materials, and the coating layer has poor structural rigidity and is easily damaged during subsequent cycling, thereby affecting the performance and service life of the battery.

[0005] The prior art provides a preparation method for an alumina-coated Ni-Co-Mn ternary lithium battery cathode material, forming a physical barrier through a simple dry coating process. However, the alumina coating layer prepared by this method is usually granular and discontinuously distributed, and cannot form a complete coating layer on the surface of the cathode material. In addition, non-active metal oxides are not conducive to charge transfer, reducing the ion transfer performance of the active material and affecting the capacity performance.

[0006] In addition, the prior art also provides a method for manufacturing a double-layer coated lithium manganese oxide material, which includes an oxide intermediate layer and a polymer outer layer, and the polymer outer layer includes a polar high molecular polymer and conductive carbon. This method obtains a positive electrode material with a uniform coating layer, but the double-layer coating further increases the resistance to charge diffusion, and the polymer outer layer has structural instability under the swelling action of the electrolyte.

[0007] The present invention is made to address the deficiencies in the above-mentioned prior art. Summary of the invention

[0008] Problem that the invention aims to solve

[0009] In order to solve the above-mentioned problems of the prior art, the present invention hopes to provide a positive electrode material compositely coated with a conductive polymer (which can conduct both electrons and ions) with a stable structure and an inorganic oxide, which can ensure the electron and ion transmission performance of the positive electrode material of the lithium-ion battery, thereby ensuring the full utilization of the battery capacity.

[0010] The present invention also aims to provide a method for preparing a composite coated lithium ion battery positive electrode material, by which the composite coated lithium ion battery positive electrode material can be obtained with simple process and high production efficiency, and is very suitable for large-scale industrial production.

[0011] Solutions for solving problems

[0012] In order to achieve the above invention purpose, the present invention adopts the following technical solution:

[0013] [1] A composite coated lithium ion battery positive electrode material, comprising a positive electrode active material core and a composite coating layer coated on the surface of the positive electrode active material core,

[0014] wherein the composite coating layer comprises a conductive polymer and an inorganic oxide,

[0015] The inorganic oxide is distributed in a dotted manner on the surface of the positive electrode active material core body,

[0016] The inorganic oxide is dispersed in the conductive polymer matrix in a dotted distribution, extending from the surface of the positive electrode active material core to the surface of the composite coating layer.

[0017] [2] The composite coated lithium ion battery positive electrode material according to [1], wherein the conductive polymer is coated on the surface of the positive electrode active material core in a network shape.

[0018] [3] The composite coated lithium ion battery positive electrode material according to [1] or [2], wherein the inorganic oxide comprises a compound selected from Al2O3, TiO2, SiO2, ZrO2, Li 0.75 La0.5 TiO3, Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li 1.5 Al 0.5 Ge 1.5 (PO4)3, Li 1.5 Al 0.5 Ge 1.5 (PO4)3,Li7La3Zr2O 12 , Li 6.55 La3Zr2Ga 0.45 O 12 , Li 2.8 Zn 0.6 GeO4, Li 3.25 Si 0.25 P 0.75 O4, Li 3.6 Ge 0.8 S 0.2 At least one of O4 and LiPON;

[0019] Preferably, the inorganic oxide is Li 1.3 Al 0.3 Ti 1.7 (PO4)3 and / or Li7La3Zr2O 12 .

[0020] [4] The composite coated lithium ion battery positive electrode material according to any one of [1] to [3], wherein the inorganic oxide is a nanoparticle with an average particle size of 10 to 500 nm, preferably 20 to 300 nm, more preferably 30 to 100 nm, and further preferably 40 to 80 nm;

[0021] Preferably, the weight ratio of the inorganic oxide to the positive electrode active material core is 0.1% to 5%, preferably 0.3% to 3%, more preferably 0.5% to 1%.

[0022] [5] A composite coated lithium ion battery positive electrode material according to any one of [1] to [4], wherein the surface area of ​​the positive electrode active material core is 100%, the area occupied by the conductive polymer is 80% to 95%, and the area occupied by the inorganic oxide distributed in a dotted manner is 5% to 20%.

[0023] [6] The composite coated lithium ion battery positive electrode material according to any one of [1] to [5], wherein the functional group of the conductive polymer comprises an alkynyl group and / or a nitrile group;

[0024] Preferably, the conductive polymer comprises at least one selected from partially cyclized polyacrylonitrile, partially cyclized polypropiolonitrile, partially cyclized polydivinylacetylene, partially cyclized propynyl acrylate / acrylonitrile copolymer, and partially cyclized methyl methacrylate / acrylonitrile copolymer;

[0025] Preferably, the thickness of the conductive polymer matrix is 5 - 200 nm, preferably 10 - 100 nm, more preferably 10 - 50 nm.

[0026] [7] The composite-coated lithium-ion battery cathode material according to any one of [1] to [6], wherein the cathode active material core includes a ternary cathode material;

[0027] Preferably, the composition of the ternary cathode material is LiNi 1-x M x O2, where 0 < x < 0.4, and M is at least two elements selected from Co, Mn, and Al;

[0028] Preferably, the ternary cathode material is a nickel cobalt manganese ternary material;

[0029] Preferably, the particle size of the ternary cathode material is 2 μm - 15 μm.

[0030] [8] A method for preparing a composite-coated lithium-ion battery cathode material according to any one of [1] to [7], the preparation method comprising the following steps:

[0031] Step (1): Mix the cathode active material core, a templating agent, and a pore-forming agent to obtain a cathode active material core coated with a template layer, and then remove the pore-forming agent to obtain a porous cathode active material core coated with a template layer;

[0032] Step (2): Mix a solution containing an inorganic oxide with the porous cathode active material core coated with a template layer, so that the inorganic oxide powder fills the pores of the template layer, and sinter to remove the template layer to obtain a cathode active material core coated with inorganic oxides distributed in dots;

[0033] Step (3): Mix the cathode active material core coated with inorganic oxides distributed in dots obtained in step (2) with a conductive polymer raw material solution to obtain a primary product; and

[0034] Step (4): Post-treat the primary product obtained in step (3) to obtain the composite-coated lithium-ion battery cathode material.

[0035] [9] The preparation method according to [8], wherein the template in step (1) comprises an acrylic polymer, wherein the acrylic polymer comprises a polymer of methyl methacrylate and / or butyl acrylate; and the pore-forming agent comprises one or more of sodium chloride, lithium chloride, and potassium chloride;

[0036] Preferably, the mass ratio of the pore-forming agent to the template agent is 1:9 to 1:5, the thickness of the template layer is 80-400 nm, and the particle size of the pore-forming agent is 100-500 nm;

[0037] Preferably, the method of removing the pore-forming agent in step (1) is water washing;

[0038] Preferably, in step (1), drying is performed before and after washing, the drying temperature is 90-120° C., and the drying time is 2-12 hours;

[0039] Preferably, the inorganic oxide solution in step (2) is a sol dispersion of inorganic oxide powder, and mixing the solution containing the inorganic oxide with the positive electrode active material core coated with the porous template layer comprises:

[0040] Dispersing inorganic oxide powder in deionized water to form a sol dispersion, adding the positive electrode active material core coated with a porous template layer into the inorganic oxide sol dispersion and stirring to obtain a mixture slurry;

[0041] Preferably, the preparation method further comprises, between step (2) and step (3), a step of dissolving at least one conductive polymer raw material in an organic solvent to obtain a conductive polymer raw material solution of a set concentration;

[0042] Preferably, the conductive polymer raw material comprises at least one selected from polyacrylonitrile, polypropylenic nitrile, polydivinyl acetylene, propynyl acrylate / acrylonitrile copolymer and methyl methacrylate / acrylonitrile copolymer;

[0043] Preferably, in the preparation method, after mixing the inorganic oxide-coated positive electrode active material distributed in dots with the conductive polymer raw material solution in step (3), stirring, filtering, washing and drying are further performed.

[0044]

[10] The preparation method according to [9], wherein the organic solvent is at least one selected from acetone, acetonitrile, tetrahydrofuran, dimethyl sulfoxide, dimethylformamide, methylpyrrolidone, dimethylacetamide and hexamethylphosphoramide;

[0045] The set concentration is 1 to 15 wt %, preferably 1 to 10 wt %.

[0046]

[11] The preparation method according to any one of [8] to

[10] , wherein in step (2), the sintering temperature ranges from 350°C to 750°C, preferably from 500°C to 650°C; and the sintering time is from 2h to 8h, preferably from 4h to 6h.

[0047]

[12] A preparation method according to any one of [8] to

[11] , wherein in step (3), the mass ratio of the inorganic oxide-coated positive electrode active material cores distributed in a dotted manner to the organic solvent used in the conductive polymer raw material solution is 1:1 to 1:15, preferably 1:1 to 1:10.

[0048]

[13] The preparation method according to any one of [9] to

[12] , wherein in step (3), the stirring temperature range is 20°C to 80°C, and the stirring time is 0.2h to 24h;

[0049] Preferably, in step (3), the drying temperature ranges from 30° C. to 120° C., and the drying time ranges from 1 h to 36 h.

[0050]

[14] The preparation method according to any one of [8] to

[13] , wherein in step (4), the post-treatment is a polymer cyclization treatment;

[0051] Preferably, the cyclization rate of the cyclization treatment is 30%-95%.

[0052] Preferably, the polymer cyclization treatment is selected from at least one of ultraviolet light treatment, heat treatment, cross-linking treatment by adding a cross-linking agent, and radiation treatment.

[0053] Preferably, the post-treatment time is 10 min to 2 h.

[0054]

[15] A lithium-ion battery, comprising the composite coated lithium-ion battery positive electrode material as described in any one of [1] to [7] or the lithium-ion battery positive electrode material prepared by the preparation method as described in any one of [8] to

[14] .

[0055] Effects of the Invention

[0056] The technical solution proposed by the present invention has the following beneficial effects:

[0057] (1) The present invention adopts a composite coating layer with a specific structure. The inorganic oxide particles are distributed in a dotted manner and extend from the surface of the positive electrode active material core to the surface of the composite coating layer, so that the inorganic oxide particles are exposed from the composite coating layer, playing the role of anchoring the conductive polymer matrix, thereby effectively suppressing the structural and functional instability of the polymer coating layer caused by swelling in the electrolyte, and solving the swelling problem of conventional polymer coating.

[0058] (2) The dot-shaped inorganic oxide particles formed on the surface of the positive electrode material of the present invention can not only anchor the polymer coating layer, but also reduce the crystallinity of the polymer and improve the ionic conductivity at room temperature.

[0059] (3) The conductive polymer coating layer used in the present invention has good mechanical and electrochemical properties. The high tensile strength and elastic deformation of the polymer itself can buffer the volume change of the electrode material during the cycle, reduce the stress accumulation of the primary particles, and maintain the integrity of the electrode structure. In addition, the conductive polymer coating layer used in the present invention has good electrolyte adsorption capacity, which can increase the wettability of the electrode and improve the liquid retention capacity.

[0060] (4) The present invention provides a composite coated positive electrode material that conducts electrons and ions by means of a template method, secondary liquid phase coating and post-treatment method, forming a uniform composite coating layer on the surface of the positive electrode material particles, providing a percolation path for lithium ion and electron transmission, and generating an isolation effect. The uniformity and functionality of the composite coating layer ensure the indispensable electron percolation in the composite coated lithium ion battery positive electrode material while suppressing the interface side reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 Schematic diagram of a double-layer composite coated positive electrode material particle;

[0062] Figure 2 This is a SEM image of the ternary positive electrode material compositely coated with the cyclized polyacrylonitrile polymer and the inorganic oxide prepared in Example 1;

[0063] Figure 3 This is a partial enlarged view of the SEM image of the ternary positive electrode material compositely coated with the cyclized polyacrylonitrile polymer and the inorganic oxide prepared in Example 1. DETAILED DESCRIPTION

[0064] Various exemplary embodiments, features and aspects of the present invention will be described in detail below. The word "exemplary" used here means "used as an example, embodiment or illustrative". Any embodiment described here as "exemplary" is not necessarily interpreted as being superior or better than other embodiments.

[0065] In addition, in order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present invention.

[0066] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values ​​and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.

[0067] In this specification, the word "may" includes both performing a certain process and not performing a certain process.

[0068] As used herein, “optional” and “optionally” mean that the subsequently described event or circumstance may or may not occur, and that the description includes instances where the event occurs and instances where it does not occur.

[0069] The term "comprising" and any variations thereof in the specification and claims of the present invention and the above drawings are intended to cover non-exclusive inclusions. For example, a process, method or system, product or device comprising a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to these processes, methods, products or devices.

[0070] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0071] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints A and B.

[0072] In this specification, when "normal temperature" or "room temperature" is used, the temperature may be 10-40°C.

[0073] <First aspect>

[0074] The first aspect of the present invention provides a composite coated lithium ion battery positive electrode material, which includes a positive electrode active material core and a composite coating layer coated on the surface of the positive electrode active material core. The composite coating layer contains a conductive polymer and an inorganic oxide, the inorganic oxide is distributed in a dotted manner on the surface of the positive electrode active material core, and the dotted inorganic oxide is dispersed in a conductive polymer matrix, extending from the surface of the positive electrode active material core to the surface of the composite coating layer.

[0075] The composite coated lithium ion battery positive electrode material of the present invention has a composite coating layer with a specific structure, and the inorganic oxide particles are distributed in a point shape and extend from the surface of the positive electrode active material core to the surface of the composite coating layer, so that the inorganic oxide particles are exposed from the composite coating layer, which plays a role in anchoring the conductive polymer matrix, thereby effectively suppressing the structural and functional instability of the polymer coating layer caused by swelling in the electrolyte, and solving the swelling problem of conventional polymer coating.

[0076] In addition to anchoring the polymer coating layer, the point-shaped inorganic oxide particles formed on the surface of the positive electrode material of the present invention can also reduce the polymer crystallinity and improve the ionic conductivity at room temperature. The conductive polymer coating layer used in the present invention can conduct both electrons and ions, and has good mechanical and electrochemical properties. The high tensile strength and elastic deformation of the high molecular polymer itself can buffer the volume change of the electrode material during the cycle, reduce the stress accumulation of the primary particles, and maintain the integrity of the electrode structure; and the polymer coating layer used in the present invention has good electrolyte adsorption capacity, which achieves the liquid retention effect by slightly swelling in the electrolyte, which can increase the wettability of the electrode and improve the liquid retention capacity.

[0077] It is understood that the conductive polymer matrix refers to a continuous medium mainly formed by a conductive polymer in which discontinuous particles are dispersed. The point distribution refers to the distribution of the particulate inorganic oxide on the surface of the positive electrode active material core with gaps and incomplete coverage.

[0078] In a further embodiment, the conductive polymer is coated on the surface of the positive electrode active material core in a mesh shape. The conductive polymer can conduct both electrons and ions, and has not only good electron / ion transport performance and liquid retention performance, but also its mesh structure has better mechanical properties.

[0079] like Figure 1 As shown, the coating layer with oxide dot distribution and the polymer coating layer form a composite coating layer on the surface of the positive electrode active material particles. A conductive polymer matrix (a continuous medium with discontinuous particles dispersed therein) is formed on the surface of the positive electrode active material core. The oxide particles extend from the surface of the positive electrode active material core to the surface of the composite coating layer. Thus, the inorganic oxide is dispersed in the polymer matrix, which can play a role in anchoring the polymer distribution and can also reduce the crystallinity of the polymer.

[0080] In an embodiment of the present invention, the inorganic oxide comprises a compound selected from the group consisting of Al2O3, TiO2, SiO2, ZrO2, Li 0.75 La 0.5 TiO3, Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li 1.5 Al0.5 Ge 1.5 (PO4)3, Li 1.5 Al 0.5 Ge 1.5 (PO4)3,Li7La3Zr2O 12 , Li 6.55 La3Zr2Ga 0.45 O 12 , Li 2.8 Zn 0.6 GeO4, Li 3.25 Si 0.25 P 0.75 O4, Li 3.6 Ge 0.8 S 0.2 At least one of O4 and LiPON; preferably, the inorganic oxide is Li 1.3 Al 0.3 Ti 1.7 (PO4)3 and / or Li7La3Zr2O 12 .

[0081] In a further embodiment, the inorganic oxide is a nanoparticle with an average particle size of 10 to 500 nm. The inorganic nano coating material can coordinate with the polymer layer to play the role of anchoring the polymer, and can also be used as a doping substance to reduce the crystallinity of the polymer and improve the ionic conductivity of the coating layer. Therefore, the smaller the particle size of the inorganic oxide, the more anchor points there are on the surface of the positive electrode active material, the larger its dispersion area in the polymer matrix, the better the effect of reducing crystallinity, and it helps to improve its ionic conductivity. However, the smaller the particle size of the inorganic oxide, the less likely it is to extend from the surface of the positive electrode active material core to the surface of the composite coating layer. Therefore, the average particle size of the inorganic oxide is preferably 20 to 300 nm, more preferably 30 to 100 nm, and further preferably 40 to 80 nm.

[0082] In a preferred embodiment, the weight ratio of the inorganic oxide to the positive electrode active material core is 0.1% to 5%, preferably 0.3% to 3%, and more preferably 0.5% to 1%.

[0083] In an embodiment of the present invention, the surface area of ​​the positive electrode active material core is 100%, the area occupied by the conductive polymer is 80% to 95%, and the area occupied by the inorganic oxide distributed in a dot shape is 5% to 20%. The larger the area of ​​the dot-shaped inorganic oxide, the better the anchoring ability, but the smaller the polymer, the smaller the elastic modulus and the weaker the liquid retention ability. From the perspective of ensuring the excellent comprehensive performance of the positive electrode material for lithium-ion batteries, the area occupied by the conductive polymer is preferably 90% to 95%, and the area occupied by the inorganic oxide distributed in a dot shape is 5% to 10%.

[0084] In the present invention, the conductive polymer is a polymer that can conduct both electrons and ions; the raw material of the conductive polymer is a polymer that can conduct ions.

[0085] In an embodiment of the present invention, the functional groups of the conductive polymer include alkynyl and / or nitrile groups. The alkynyl and / or nitrile groups can coordinate with transition metal ions in the cathode material to form a metal-organic coordination structure, realizing the adsorption of the polymer on the surface. In a further embodiment, the conductive polymer includes at least one selected from partially cyclized polyacrylonitrile, partially cyclized polypropiolonitrile, partially cyclized polydivinylacetylene, partially cyclized propynyl acrylate / acrylonitrile copolymer, and partially cyclized methyl methacrylate / acrylonitrile copolymer; the raw material of the conductive polymer in the present invention includes at least one selected from polyacrylonitrile, polypropiolonitrile, polydivinylacetylene, propynyl acrylate / acrylonitrile copolymer, and methyl methacrylate / acrylonitrile copolymer. These polymers have the ability to conduct ions. After cyclization treatment, these polymers have both the ability to conduct electrons and ions; the cyclization rate is 30% - 95%, preferably 50% - 90%, more preferably 60% - 80%.

[0086] In a further embodiment, the thickness of the conductive polymer matrix is 5 - 200 nm, preferably 10 - 100 nm, more preferably 10 - 50 nm. Preferably, the thickness of the polymer matrix is less than the particle size of the inorganic oxide, so that the inorganic oxide can be easily exposed on the surface of the composite coating layer. However, agglomeration between inorganic oxides can also extend to the polymer surface to achieve exposure, so the thickness of the polymer matrix can also be slightly greater than the particle size of the inorganic oxide.

[0087] In an embodiment of the present invention, the cathode active material core includes a ternary cathode material. Preferably, the composition of the ternary cathode material is LiNi 1-x M x O2, where 0 < x < 0.4, and M is at least two elements selected from Co, Mn, and Al; more preferably, the ternary cathode material is a nickel-cobalt-manganese ternary material.

[0088] In a further embodiment, the particle size of the ternary cathode material is 2 μm - 15 μm.

[0089] <Second aspect>

[0090] The second aspect of the present invention provides a method for preparing a composite-coated lithium-ion battery cathode material, the preparation method including the following steps:

[0091] Step (1): mixing a positive electrode active material core, a template agent and a pore-forming agent to obtain a positive electrode active material core coated with a template layer, and then removing the pore-forming agent to obtain a positive electrode active material core coated with a porous template layer;

[0092] Step (2): mixing a solution containing an inorganic oxide with a positive electrode active material core body coated with a porous template layer, filling the inorganic oxide powder into the pores of the template layer, sintering to remove the template layer, and obtaining a positive electrode active material core body coated with an inorganic oxide with dot distribution;

[0093] Step (3): mixing the inorganic oxide-coated positive electrode active material cores with dot distribution obtained in step (2) with a conductive polymer raw material solution to obtain a primary product; and

[0094] Step (4): post-treating the primary product obtained in step (3) to obtain the composite coated lithium ion battery positive electrode material.

[0095] The present invention firstly adopts a template method to coat a template layer on the surface of the core of the positive electrode active material, and forms pores in the template layer, leaving pores filled with inorganic oxides, and then adopts a liquid phase coating method to fill the inorganic oxides into the pores. After removing the template, the inorganic oxides are distributed in the form of dots extending outward on the surface of the core of the positive electrode active material; then, liquid phase coating is used again to coat the ion-conducting conductive polymer raw material on the surface of the positive electrode active material, and the inorganic oxides distributed in dots on the surface of the positive electrode active material are dispersed in the conductive polymer matrix, and the conductive polymer raw material is anchored on the surface of the core of the positive electrode active material; finally, through post-treatment, the conductive polymer raw material is made to have electronic conductivity.

[0096] The present invention provides a composite coated positive electrode material that conducts electrons and ions by means of a template method, secondary liquid phase coating and post-treatment, and forms a uniform composite coating layer on the surface of the positive electrode material particles, providing a percolation path for lithium ion and electron transmission and generating an isolation effect. The uniformity and functionality of the composite coating layer ensure the indispensable electron percolation in the composite coated lithium ion battery positive electrode material while suppressing the interface side reaction.

[0097] In an embodiment of the present invention, the template in step (1) comprises an acrylate polymer, and the acrylate polymer comprises a polymer of methyl methacrylate and / or butyl acrylate. In a further embodiment, the pore-forming agent comprises one or more of sodium chloride, lithium chloride, and potassium chloride. Preferably, one or more of nano sodium chloride, nano lithium chloride, and nano potassium chloride can be selected and used.

[0098] In an embodiment of the present invention, the mass ratio of the pore former to the template agent is 1:9 to 1:5, the thickness of the template layer is 80 to 400 nm, and the particle size of the pore former is 100 to 500 nm. In a preferred embodiment, the particle size of the pore former is greater than the thickness of the template layer, so that after the pore former is removed, the pores on the template layer can extend from the surface of the positive electrode active material core to the surface of the template layer, thereby further ensuring that the inorganic oxide filled in the pores can contact the surface of the positive electrode active material core to be fixed and exposed on the surface of the template layer.

[0099] In a preferred embodiment, the thickness of the template layer is greater than the thickness of the conductive polymer matrix finally formed, so that the height of the pores in the template layer is greater than the thickness of the conductive polymer matrix, further ensuring that the inorganic oxide can extend to the surface of the composite coating layer.

[0100] In an embodiment of the present invention, the pore-forming agent is removed in step (1) by water washing. In a further embodiment, drying is performed before and after water washing in step (1), the drying temperature is 90-120° C., and the drying time is 2-12 hours.

[0101] In a further embodiment, the step (2) of mixing the solution containing the inorganic oxide with the positive electrode active material core coated with the porous template layer includes: dispersing the inorganic oxide powder in deionized water to form a sol dispersion, adding the positive electrode active material core coated with the porous template layer into the inorganic oxide sol dispersion and stirring to obtain a mixture slurry.

[0102] In a further embodiment, the preparation method of the present invention further comprises, between step (2) and step (3), a step of dissolving at least one conductive polymer in an organic solvent to obtain a conductive polymer raw material solution of a set concentration. In a further embodiment, the set concentration of the conductive polymer raw material solution is 1 to 15 wt %, preferably 1 to 10 wt %.

[0103] In a preferred embodiment, in the preparation method of the present invention, after mixing the inorganic oxide-coated positive electrode active material distributed in dots with the conductive polymer raw material solution in step (3), stirring, filtering, washing and drying are further performed.

[0104] In an embodiment of the present invention, the organic solvent is at least one selected from acetone, acetonitrile, tetrahydrofuran, dimethyl sulfoxide, dimethylformamide, methyl pyrrolidone, dimethylacetamide and hexamethylphosphoramide.

[0105] In an embodiment of the present invention, in step (1), the sintering temperature ranges from 350°C to 750°C, preferably from 500°C to 650°C; and the sintering time ranges from 2h to 8h, preferably from 4h to 6h.

[0106] In step (3), the mass ratio of the inorganic oxide-coated positive electrode active material cores distributed in a dotted manner to the organic solvent used in the conductive polymer raw material solution is 1:1 to 1:15, preferably 1:1 to 1:10.

[0107] In step (3), the stirring temperature ranges from 20°C to 80°C, and the stirring time ranges from 0.2h to 24h. In a preferred embodiment, in step (3), the drying temperature ranges from 30°C to 120°C, and the drying time ranges from 1h to 36h.

[0108] In step (4), the post-treatment is a polymer cyclization treatment. The cyclization rate of the cyclization treatment is 30% to 95%, preferably 50% to 90%, and more preferably 60% to 80%. In a preferred embodiment, the polymer cyclization treatment is selected from at least one of ultraviolet light treatment, heat treatment, cross-linking treatment by adding a cross-linking agent, and radiation treatment. The cyclization reaction of the polymer coating layer in the present invention forms a delocalized sp 2 π bond, so that the cyclized coating has electronic conductivity. The uncyclized polymer has a certain ionic conductivity, combined with nano-scale inorganic oxide particles, to ensure that the coating has a low ion migration barrier, thereby forming a complete and continuous electronic and ion conductive network on the surface of the active material particles. The degree of swelling of the polymer coating in the electrolyte is controlled by the degree of polymer cyclization, so that the degree of polymer cyclization can be appropriately controlled to obtain a polymer coating with excellent liquid retention effect.

[0109] In the present invention, there is no particular restriction on the time of post-treatment, but from the viewpoint of economic benefit and ensuring the appropriate performance and cyclization degree of the obtained lithium ion battery positive electrode material, the time of post-treatment is 10 minutes to 2 hours.

[0110] In summary, the present invention provides a composite coated positive electrode material that conducts electrons / ions through a template method, secondary liquid phase coating and post-treatment methods; the polymer with an acetylenic or nitrile group interacts with the transition metal of the positive electrode material to form an adsorption, and further crosslinks and cyclizes on the surface of the material to form a uniform composite coating layer on the surface of the positive electrode material particles, providing a percolation path for lithium ion / electron transmission and producing an isolation effect. The uniformity and functionality of the composite coating layer ensure the indispensable electron percolation in the composite positive electrode while suppressing the interface side reactions.

[0111] <Third Aspect>

[0112] A third aspect of the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the composite coated lithium ion battery positive electrode material as described above or the lithium ion battery positive electrode material prepared by the preparation method as described above.

[0113] Since the lithium ion battery positive electrode material of the present invention suppresses the interface side reaction while ensuring the indispensable electron percolation in the composite positive electrode due to the uniformity and functionality of the composite coating layer, and also has good electrolyte adsorption capacity, the lithium ion battery using the lithium ion battery positive electrode material of the present invention can ensure excellent battery performance and good safety performance.

[0114] Example

[0115] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0116] Example 1

[0117] 10g of uncoated LiNi 0.8 Co 0.1 Mn 0.1 O2 ternary material (mass ratio to coating material is 100:1), 1g of polymethyl methacrylate as a template and 0.15g of sodium chloride (average particle size is 200nm) as a pore-forming agent are mixed together to obtain a ternary material core coated with a template layer, wherein the thickness of the template layer is 150nm.

[0118] The ternary material core body coated with the template layer was dried at 80°C for 6 hours. Then, the pore-forming agent was removed by water washing to obtain a positive electrode active material core body coated with a porous template layer. Next, the positive electrode active material core body coated with a porous template layer was dried at 90°C for 12 hours to obtain a dried treated positive electrode active material core body.

[0119] 0.1 g of Li with a particle size of 50 nm was added 1.3 Al 0.3 Ti 1.7 (PO4)3(LATP) was dispersed in deionized water and stirred to form a uniformly dispersed sol dispersion. 10g of the treated positive electrode active material core was slowly added to the LATP dispersion and stirred at 65°C to obtain a mixture slurry, and the solvent was finally completely evaporated to obtain a precursor. The precursor was placed in a sintering furnace, the sintering temperature was set to 550°C, and sintered for 6 hours to obtain a ternary material coated with an inorganic oxide with a dot distribution;

[0120] Accurately weigh 1g (molecular weight 150,000) of polyacrylonitrile, the specific structural formula is as follows:

[0121]

[0122] Add it into a beaker containing 34g of dimethylformamide, seal it and stir it at room temperature for 20 minutes to obtain a conductive polymer raw material solution. Add 10g of the above-mentioned ternary material coated with inorganic oxide to the conductive polymer raw material solution, stir and disperse it at 45°C for 5h, and then dry the mixture at 80°C for 10h. Finally, the dried material is heat-treated and cyclized at 220°C for 1h to finally obtain a ternary positive electrode material with a cyclization rate of 50% and a composite coating of polyacrylonitrile polymer and inorganic oxide, wherein the surface area of ​​the ternary positive electrode material is 100%, the area ratio occupied by the cyclized polyacrylonitrile polymer is 90%, and the area ratio occupied by the inorganic oxide LATP distributed in a point shape is 10%; Figure 2 shown.

[0123] The composite coated ternary cathode material obtained in Example 1 was measured using an electron scanning microscope at a magnification of 5,000 times. The obtained SEM image is as follows: Figure 2 and Figure 3 As shown. Figure 2 It can be seen that the morphology of the composite coated ternary cathode material is a secondary sphere assembled from primary particles; further, Figure 3 for Figure 2 A partial enlarged view of the area within the box, from Figure 3 The enlarged image shows that the cyclized polyacrylonitrile polymer is coated on the surface of the ternary cathode material core. The inorganic oxide LATP corresponds to the white dot-like portion on the outermost surface (e.g., the small dot-like portion pointed by the arrow), which is distributed in the cyclized polyacrylonitrile polymer in a dot-like manner and is exposed.

[0124] Example 2

[0125] In addition to replacing the conductive polymer raw material polyacrylonitrile with polyacrylonitrile, the inorganic oxide LATP was replaced with Li7La3Zr2O with a particle size of 40nm. 12 Except for the above, the rest is the same as Example 1. Finally, a ternary positive electrode material of a polypropylonitrile polymer with a cyclization rate of 45% and an inorganic oxide composite coating is obtained, wherein the surface area of ​​the ternary positive electrode material is 100%, the area ratio occupied by the cyclized polypropylonitrile polymer is 90%, and the area ratio occupied by the inorganic oxide distributed in a dotted manner is 10%.

[0126] Example 3

[0127] The method is the same as that of Example 1 except that the conductive polymer raw material polyacrylonitrile is replaced by propynyl acrylate / acrylonitrile copolymer and the inorganic oxide LATP is replaced by LATP with a particle size of 80 nm.

[0128] Example 4

[0129] Except that the particle size of the inorganic oxide LATP is replaced with 30 nm, the rest is the same as Example 1.

[0130] Example 5

[0131] Except that the particle size of the inorganic oxide LATP is replaced with 100 nm, the rest is the same as Example 1.

[0132] Example 6

[0133] Except that the weight ratio of inorganic oxide to the positive electrode active material core body is replaced with 0.1%, the rest is the same as Example 1.

[0134] Example 7

[0135] Except that the weight ratio of inorganic oxide to the positive electrode active material core body is replaced with 0.5%, the rest is the same as Example 1.

[0136] Example 8

[0137] Except that the weight ratio of the inorganic oxide to the positive electrode active material core body is replaced with 5%, the rest is the same as Example 1.

[0138] Example 9

[0139] The method is the same as that in Example 1 except that the mass ratio of the pore former to the template is 1:4, so that the conductive polymer occupies 75% of the area and the inorganic oxide occupies 25% of the area.

[0140] Example 10

[0141] The method is the same as that of Example 1 except that the mass ratio of the pore former to the template is 1:10, so that the area ratio occupied by the conductive polymer is 97% and the area ratio occupied by the inorganic oxide is 3%.

[0142] Embodiment 11

[0143] Except that the concentration of the conductive polymer raw material solution is 1 wt %, the rest is the same as that of Example 1.

[0144] Example 12

[0145] Except that the concentration of the conductive polymer raw material solution is 10 wt %, the rest is the same as that of Example 1.

[0146] Embodiment 13

[0147] Except that the inorganic oxide LATP is replaced by Al2O3, everything else is the same as Example 1.

[0148] Embodiment 14

[0149] Except that the conductive polymer raw material polyacrylonitrile is replaced by polymethyl acrylate, the rest is the same as Example 1.

[0150] Embodiment 15

[0151] Except that the heat treatment time of the cyclization is changed to 2 hours so that the cyclization rate of the cyclization treatment is 80%, the rest is the same as Example 1. Finally, a ternary positive electrode material compositely coated with a polyacrylonitrile polymer and an inorganic oxide with a cyclization rate of 80% is obtained, wherein the surface area of ​​the ternary positive electrode material is 100%, the area ratio occupied by the cyclized polyacrylonitrile polymer is 90%, and the area ratio occupied by the inorganic oxide LATP distributed in a dot shape is 10%.

[0152] Comparative Example 1

[0153] Compared with Example 1, this comparative example does not add a template agent and a pore-forming agent, and the other parameters such as the types of raw materials and the amount of feed are the same as those in Example 1. The preparation method of this comparative example is:

[0154] Disperse LATP in deionized water and stir to form a uniformly dispersed sol dispersion. 0.8 Co 0.1 Mn 0.1 The O2 ternary material is slowly added to the LATP dispersion, stirred at 65°C to obtain a mixture slurry, and finally the solvent is completely evaporated to obtain a precursor. The precursor is placed in a sintering furnace, the sintering temperature is set to 550°C, and sintered for 6 hours to obtain a layered inorganic oxide-coated ternary material; then the inorganic oxide-coated ternary material is added to the conductive polymer raw material solution of polyacrylonitrile, stirred and dispersed at 45°C for 5 hours, and then the mixture is dried at 80°C for 10 hours. Finally, the dried material is heat-treated at 220°C for cyclization for 1 hour, and finally a double-layer-coated ternary positive electrode material with an inner layer of inorganic oxide and an outer layer of polyacrylonitrile polymer with a cyclization rate of 50% is obtained.

[0155] Comparative Example 2

[0156] Compared with Example 1, this comparative example does not add a template agent and a pore-forming agent, and the other parameters such as the types of raw materials and the amount of feed are the same as those in Example 1. The preparation method of this comparative example is:

[0157] LATP and polyacrylonitrile were dispersed into the solution and stirred to form a uniformly dispersed polymer-inorganic oxide solution. 0.8 Co 0.1 Mn 0.1The O2 ternary material was slowly added to the polymer-inorganic oxide solution, and after being stirred and dispersed at 45°C for 5 hours, the mixture was dried at 80°C for 10 hours. Finally, the dried material was heat-treated at 220°C for 1 hour to obtain a ternary positive electrode material coated with a mixed monolayer of polyacrylonitrile polymer and inorganic oxide with a cyclization rate of 50%.

[0158] Comparative Example 3

[0159] Except for not performing the cyclization treatment, the rest is consistent with Example 1. Finally, a ternary positive electrode material with a double layer of uncyclized polyacrylonitrile polymer and inorganic oxide is obtained.

[0160] Test method:

[0161] Accurately weigh 9g of partially cyclized polymer-coated ternary cathode material, 0.5g of polyvinylidene fluoride (PVDF) and 0.5g of conductive carbon black, grind for 5min and mix evenly. Then put the mixture into N-methylpyrrolidone and stir for 30min to form a uniform slurry. Use a scraper to apply the stirred slurry on a 12μm aluminum foil and dry it at 110℃ in vacuum for 3h. Use a punching machine to make an electrode disc with a diameter of 14mm, use lithium metal as the negative electrode, and use a mixed solution of 1mol / L LiPF6 (solvent is ethylene carbonate and propylene carbonate, volume ratio 3:7) as the electrolyte. Assemble CR2032 button half-cell in an argon glove box. The half-cell is charged and discharged in the voltage range of 2.8~4.3V, and the current density of 1C is 180mA / g.

[0162] The partially cyclized / uncyclized polymer-coated ternary cathode materials in Examples 1-15 and Comparative Examples 1-3 were subjected to cycle and rate performance tests at room temperature (25°C) using a button cell battery testing system. The cycle test used a current density of 1C to compare the capacity retention rates after 50 cycles. The rate test used rates of 1C, 2C, 3C, 4C, and 5C to test the capacity retention rates, and finally compared the capacity retention rates at 5C. The test results are shown in Table 1.

[0163] Table 1

[0164]

[0165] By comparing the embodiments of the present invention with the comparative examples, it can be seen that the composite coated lithium ion battery positive electrode material of the specific structure and material prepared by the present invention has a stable coating layer structure, provides a percolation path for lithium ion and electron transmission, and produces an isolation effect, has good ion and electron conductivity, and inhibits interface side reactions while ensuring the indispensable electron percolation in the composite coated lithium ion battery positive electrode material. Therefore, embodiments 1-15 have good cycle performance and rate performance compared with comparative examples 1-3.

[0166] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.

[0167] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A composite coated lithium ion battery positive electrode material, characterized in that: It comprises a positive electrode active material core and a composite coating layer coated on the surface of the positive electrode active material core. The composite coating layer comprises a conductive polymer and an inorganic oxide, wherein the conductive polymer comprises at least one selected from partially cyclized polyacrylonitrile, partially cyclized polypropylonitrile, partially cyclized polydivinyl acetylene, partially cyclized propynyl acrylate / acrylonitrile copolymer and partially cyclized methyl methacrylate / acrylonitrile copolymer, and the inorganic oxide comprises at least one selected from Al2O3, TiO2, SiO2, ZrO2, Li 0.75 La 0.5 TiO3, Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li 1.5 Al 0.5 Ge 1.5 (PO4)3, Li 1.5 Al 0.5 Ge 1.5 (PO4)3,Li7La3Zr2O 12 , Li 6.55 La3Zr2Ga 0.45 O 12 , Li 2.8 Zn 0.6 GeO4, Li 3.25 Si 0.25 P 0.75 O4, Li 3.6 Ge 0.8 S 0.2 At least one of O4 and LiPON, The inorganic oxide is distributed in a dotted manner on the surface of the positive electrode active material core body, The inorganic oxide is dispersed in a conductive polymer matrix in a dotted manner, extending from the surface of the positive electrode active material core to the surface of the composite coating layer, The composite coated lithium ion battery positive electrode material is obtained by a preparation method comprising the following steps: Step (1): mixing a positive electrode active material core, a template agent and a pore-forming agent to obtain a positive electrode active material core coated with a template layer, and then removing the pore-forming agent to obtain a positive electrode active material core coated with a porous template layer; Step (2): mixing a solution containing an inorganic oxide with a positive electrode active material core body coated with a porous template layer, so that the inorganic oxide fills the pores of the template layer, and sintering to remove the template layer to obtain a positive electrode active material core body coated with an inorganic oxide with dot distribution; Step (3): mixing the inorganic oxide-coated positive electrode active material cores with dot distribution obtained in step (2) with a conductive polymer raw material solution to obtain a primary product; and Step (4): post-treating the primary product obtained in step (3) to obtain the composite coated lithium ion battery positive electrode material.

2. The composite coated lithium ion battery positive electrode material according to claim 1, wherein the conductive polymer is coated on the surface of the positive electrode active material core in a network shape.

3. The composite coated lithium ion battery positive electrode material according to claim 1 or 2, wherein the inorganic oxide is Li 1.3 Al 0.3 Ti 1.7 (PO4)3 and / or Li7La3Zr2O 12 . 4 . The composite coated lithium ion battery positive electrode material according to claim 1 , wherein the inorganic oxide is a nanoparticle with an average particle size of 10 to 500 nm. 5 . The composite coated lithium ion battery positive electrode material according to claim 4 , wherein the weight ratio of the inorganic oxide to the positive electrode active material core is 0.1% to 5%.

6. The composite coated lithium ion battery positive electrode material according to claim 1 or 2, wherein the surface area of ​​the positive electrode active material core is 100%, the area ratio occupied by the conductive polymer is 80% to 95%, and the area ratio occupied by the inorganic oxide distributed in a dotted manner is 5% to 20%.

7. The composite coated lithium ion battery positive electrode material according to claim 1 or 2, wherein the thickness of the conductive polymer matrix is ​​5 to 200 nm.

8. The composite coated lithium ion battery positive electrode material according to claim 1 or 2, wherein the positive electrode active material core comprises a ternary positive electrode material.

9. The composite-coated lithium-ion battery cathode material according to claim 8, wherein the composition of the ternary cathode material is LiNi 1-x M x O2, where 0 < x < 0.4, and M is at least two elements selected from Co, Mn, and Al. 10 . The composite coated lithium ion battery positive electrode material according to claim 8 , wherein the ternary positive electrode material is a nickel-cobalt-manganese ternary material. 11 . The composite coated lithium ion battery positive electrode material according to claim 8 , wherein the particle size of the ternary positive electrode material is 2 μm to 15 μm.

12. A method for preparing a composite coated lithium ion battery positive electrode material according to any one of claims 1 to 11, characterized in that: The preparation method comprises the following steps: Step (1): mixing a positive electrode active material core, a template agent and a pore-forming agent to obtain a positive electrode active material core coated with a template layer, and then removing the pore-forming agent to obtain a positive electrode active material core coated with a porous template layer; Step (2): mixing a solution containing an inorganic oxide with a positive electrode active material core body coated with a porous template layer, so that the inorganic oxide fills the pores of the template layer, and sintering to remove the template layer to obtain a positive electrode active material core body coated with an inorganic oxide with dot distribution; Step (3): mixing the inorganic oxide-coated positive electrode active material cores with dot distribution obtained in step (2) with a conductive polymer raw material solution to obtain a primary product; and Step (4): post-treating the primary product obtained in step (3) to obtain the composite coated lithium ion battery positive electrode material.

13. The preparation method according to claim 12, wherein the template in step (1) comprises an acrylate polymer, the acrylate polymer comprises a polymer of methyl methacrylate and / or butyl acrylate; and the pore-forming agent comprises one or more of sodium chloride, lithium chloride, and potassium chloride. 14 . The preparation method according to claim 13 , wherein the mass ratio of the pore-forming agent to the template agent is 1:9 to 1:5, the thickness of the template layer is 80-400 nm, and the particle size of the pore-forming agent is 100-500 nm.

15. The preparation method according to claim 13, wherein the method of removing the pore-forming agent in step (1) is water washing.

16. The preparation method according to claim 15, wherein in step (1), drying is performed before and after washing, the drying temperature is 90-120°C, and the drying time is 2-12h.

17. The preparation method according to claim 13, wherein the inorganic oxide solution in step (2) is a sol dispersion of inorganic oxide powder, and mixing the inorganic oxide solution with the positive electrode active material core coated with the porous template layer comprises: The inorganic oxide powder is dispersed in deionized water to form a sol dispersion liquid, and the positive electrode active material core body coated with a porous template layer is added into the inorganic oxide sol dispersion liquid and stirred to obtain a mixture slurry.

18. The preparation method according to claim 13, wherein the preparation method further comprises, between step (2) and step (3), a step of dissolving at least one conductive polymer raw material in an organic solvent to obtain a conductive polymer raw material solution of a set concentration.

19. The preparation method according to claim 13, wherein the conductive polymer raw material comprises at least one selected from the group consisting of polyacrylonitrile, polypropiolonitrile, polydivinylene, propiolyl acrylate / acrylonitrile copolymer and methyl methacrylate / acrylonitrile copolymer.

20. The preparation method according to claim 13, wherein in step (3), after mixing the inorganic oxide-coated positive electrode active material distributed in dots with the conductive polymer raw material solution, the preparation method further performs stirring, filtering, washing and drying operations.

21. The preparation method according to claim 18, wherein the organic solvent is at least one selected from acetone, acetonitrile, tetrahydrofuran, dimethyl sulfoxide, dimethylformamide, methyl pyrrolidone, dimethylacetamide and hexamethylphosphoramide.

22. The preparation method according to claim 18, wherein the set concentration is 1 to 15 wt%.

23. The preparation method according to any one of claims 12 to 22, wherein in the step (2), the sintering temperature ranges from 350°C to 750°C; and the sintering time is from 2h to 8h.

24. The preparation method according to any one of claims 12 to 22, wherein in the step (3), the mass ratio of the inorganic oxide-coated positive electrode active material cores distributed in a dotted manner to the organic solvent used in the conductive polymer raw material solution is 1:1 to 1:

15.

25. The preparation method according to any one of claims 13 to 22, wherein in the step (3), the stirring temperature ranges from 20°C to 80°C, and the stirring time ranges from 0.2h to 24h.

26. The preparation method according to claim 25, wherein in the step (3), the drying temperature ranges from 30°C to 120°C, and the drying time ranges from 1 hour to 36 hours.

27. The preparation method according to any one of claims 12 to 22, wherein in the step (4), the post-treatment is a polymer cyclization treatment.

28. The preparation method according to claim 27, wherein the cyclization rate of the cyclization treatment is 30%-95%.

29. The preparation method according to claim 27, wherein the polymer cyclization treatment is selected from at least one of ultraviolet light treatment, heat treatment, cross-linking treatment by adding a cross-linking agent, and radiation treatment.

30. The preparation method according to claim 27, wherein the post-treatment time is 10 min to 2 h.

31. A lithium ion battery, characterized in that: The lithium-ion battery comprises the composite-coated lithium-ion battery positive electrode material according to any one of claims 1 to 11 or the lithium-ion battery positive electrode material prepared by the preparation method according to any one of claims 12 to 30.

Citation Information

Patent Citations

  • Self-healing laminar positive electrode material with three-dimensional Li&lt;+&gt; diffusion path and preparation method of self-healing laminar positive electrode material

    CN105576219A

  • Composite material adopting conductive electron / conductive ion polymer to coat ternary positive electrode material and preparation method thereof

    CN113097465A